The Influence of Leadership and Organizational Culture on Performance through Compensation for Employees of the Directorate General of the General Judicial Body of the Supreme Court Republic of Indonesia - Puji Mulyani; Harry Indra Tjahyo; Iwan Kurniawan (Krisnadwipayana International Journal of Management Studies, 2023)
This research aims to examine the influence of leadership and organizational culture on performance through employee compensation. This research uses quantitative methods by distributing questionnaires to employees of the Directorate General of General Justice of the Supreme Court of the Republic of Indonesia. The population of this research is all Civil Servant s of the Directorate General of General Justice, totaling 113 people within the Directorate General of General Justice. The sampling technique in this research used the Slovin formula. The data analysis method used in this research is multiple linear regression and simple linear regression, namely the F test and T test. This research shows that simultaneously leadership and organizational culture have a positive and significant effect on compensation at the Directorate General of General Justice of the Supreme Court of the Republic of Indonesia. This can be seen from the calculated F value of 122.134. And the R square value is 0.830 or 83% with a significance probability value of 0.000 < 0.05.